Vision impairment and refractive errors in refugees presenting to community optometry clinics in Victoria, Australia. (26th November 2019) - Selvarajah, Suganya; Dunt, David R; Marella, Manjula; Hewitt, Alex W; Turner, Neville; Carozzi, Piers; Napper, Genevieve; Jackson, Jonathan A
Abstract : Background: There is a paucity of data relating to refugee eye health in Australia. This study aimed at investigating the spectrum of vision impairment and other ocular conditions in refugees utilising the Victorian Eyecare Service operated by the Australian College of Optometry. Methods: A cross‐sectional study of electronic clinical records of 518 individuals (adults and children) recognised as refugees by the Australian College of Optometry and treated between January 2013 and May 2014 were identified. Extracted data included presenting visual acuities, best‐corrected visual acuities, and final refraction values (using spherical equivalents), for both eyes. Diagnoses of presenting ocular conditions were also extracted. Results: Of all refugees examined, 129 (27.2 per cent) had some degree of vision impairment (≤ 6/9.5) based on presenting visual acuities in their better eye; five (1.0 per cent) being of a severe (≤ 6/60) or profound (≤ 6/120) nature. In contrast, 27 (6.3 per cent) refugees had some degree of vision impairment based on best‐corrected visual acuities in their better eye; two (0.4 per cent) being of a severe or profound nature. The prevalence of myopia (≥ −0.50 D) in the better eye was 23.0 per cent (n = 114); 25 (5.0 per cent) being moderate (≥ −3.00 D) to high (≥ −6.00 D). The prevalence of hypermetropia (≥ +2.00 D) in the better eye was 3.2 per cent (n = 16); 12 (2.4 per cent) being moderate (≥ +2.25 D) to high (≥ +5.25 D). The most common ocular conditions diagnosed at initial presentation were refractive error (n = 104, 20.1 per cent) and dry eyes (n = 57, 11.0 per cent). Conclusion: Mild vision impairment and refractive error are significant issues for refugees attending the Australian College of Optometry, emphasising the need for optometry, particularly refractive, services in this population.